Duino Elegies - Rilke, Rainer Maria (New York W. W. Norton and Company, Inc., 1963)
The Duino Elegies count as Rainer Maria Rilkes last great work, the ultimate expression of his spiritual experience. They are named for the Castle of Duino, which stands on a rocky headland of the Adriatic above Trieste where, during a lonely winter sojourn in 1912, some of them were first conceived. Ten years of distressing silence followed this promising beginning, and then, in another lonely castle in Switzerland, the spell was broken and ten elegies took shape. "All in a few days, it was an indescribable storm, a mental and spiritual hurricane (as in those days at Duino), every fibre, every tissue in me cracked eating was never to be thought of, God knows what nourished me."- Stephen Spender has collaborated with J.B. Leishman in this translation. The original German text is printed opposite each translation, and Mr. Leishman has provided a forward, a commentary, and appendicies.
Keywords: Poetry